Chelate cooperativity effects on the formation of di- and trivalent pseudo[2]rotaxanes with diketopiperazine threads and tetralactam wheels. Issue 44 (14th September 2015) - Traulsen, Nora L.; Traulsen, Christoph H.-H.; Deutinger, Peter M.; Müller, Sebastian; Schmidt, Deborah; Linder, Igor; Schalley, Christoph A.
Abstract : Double mutant cycle analyses of isothermal titration calorimetry data on di- and trivalent amide pseudorotaxanes provide insight into chelate cooperativity effects on multiply threaded structures. Abstract : The formation of singly, doubly and triply threaded pseudo[2]rotaxanes with diketopiperazine threads and tetralactam wheels is investigated with respect to chelate cooperativity effects on multivalent binding. Two series of guest molecules are prepared which differ with respect to their spacers, one with preorganised centrepieces with di- or tripodal roof-like structures, one with more flexible spacers. The thermodynamics of pseudorotaxane formation is examined using isothermal titration calorimetry and 1 H NMR spectroscopy. Force-field calculations provide more detailed structural insight and help rationalizing the thermodynamic data. All di- and trivalent pseudorotaxanes exhibit positive chelate cooperativity presumably arising from spacer–spacer interactions. Higher cooperativity factors are observed for the more preorganised threads.